Kesalahan Berbahasa pada Aspek Ejaan, Diksi, Imbuhan, dan Struktur Kalimat dalam Karangan Cerita Pendek Siswa - Wahyudi Wahyudi; E. Zaenal Arifin (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2021)
This study aims to determine the types and patterns of errors that occur in short story writing in trilingual students of grade VII at Tzu Chi International School, so that the types and patterns of language errors can be used as guidelines in compiling teaching materials for short story writing in an international schools (SPK). The method in this study is a qualitative descriptive method. The source of the data for this research is a short story that written by grade VII Tzu Chi International School students. The results obtained from 32 samples there were 316 errors consisting of errors in spelling, diction, affixes, and sentence structure aspects. The most language errors were in the spelling aspect, totally 114 errors (36%) including errors in writing capital letters, writing pronouns, writing prepositions, writing acronyms, rewriting words, writing numbers, using absorption words, and using punctuation marks, then errors on the diction aspect, there are 85 errors (26.8 %), including errors in finding the appropriate form (suitable) with the situation and the sense of Bahasa Indonesia native speakers. Errors in the affix aspect 80 errors (25.3%), which included errors in the omission of the affix field and in the word formation, errors in sounds that should have melted, but were not melted, errors in the yielding of sounds that should not have melted, replacement and shortening of morphs, and the use of inappropriate affixes and errors in the aspect of sentence structure as many as 37 errors (11.7%) including excessive wording and use of elements, unsubjected sentence errors, unpredicated sentences, and ambiguous sentences. Keywords: Language errors, diction aspect, spelling aspect, affix aspect, sentence structure aspect and ability to write short stories